AN ECONOMIC RESILIENCE OF FAMILIES IN PANDEMIC OUTBREAK: A LITERATURE REVIEW APPROACH - Etty Susilowati (President University, 2021)
The Covid-19 pandemic is able to change all aspects of people's lives, especially in Indonesia, including economic resilience of families during the pandemic period. Resilience does not only apply to industry or other business institutions, but also to the family entity. This study aims to analyze through literature review approach to develop a conceptual model of family economic resilience during a pandemic. There is a lot of literature that has explained the concept of resilience for business organizations since the 1990s, especially alongside with the introduction of the concept of business continuity. Along with the covid-19 pandemic, the development of literature related to business and organizational resilience is also increasing. Using a literature review approach, this study identifies several factors that can form the concept. Several protective factors in the psychological approach make it possible to form this concept, as well as other attributes including rebounding/ reintegration, high expectancy/family determination, positive relationship/social support, flexibility, and family self-esteem/self-efficacy. Even further also some literature finds the power of resilience for business when it was built by the family or the so-called home- based business in times of crisis. The theoretical implications and further research agenda will also be the subject of future discussion and be significant findings for other researchers and policymakers. Keywords: family, economic resilience, home based business, pandemic